Dark tourists: Are almost all of us - Martins, Rui (2022)
Experiencing places associated with death is not a recent phenomenon. For a long time, people have been attracted to sites, attractions or events that somehow are associated with death or disaster. War related sites possibly constitute one of the largest categories of tourist attractions worldwide. This study raises the question of whether Dark Tourism is only of interest to a niche of tourists or if there is the desire and motivation in each of us to have a dark experience. One can conclude that, consciously or unconsciously, man in general is attracted to practice this type of tourism, and frequently not even the tourist realizes that his motivations are linked to the proximity of death and disaster.